Lightweight, efficient, robust epidemic dissemination - Matos, Miguel (2013)
Today's intensive demand for data such as live broadcast or news feeds requires effcient and robust dissemination systems. Traditionally, designs focus on extremes of the effciency/robustness spectrum by either using structures, such as trees for effciency or by using loosely-coupled epidemic protocols for robustness. We present Brisa, a hybrid approach combining the robustness of epidemics with the effciency of structured approaches. Brisa implicitly emerges embedded dissemination structures from an underlying epidemic substrate. The structures' links are chosen with local knowledge only, but still ensuring connectivity. Failures can be promptly compensated and repaired thanks to the epidemic substrate, and their impact on dissemination delays masked by the use of multiple independent structures. Besides presenting the protocol design, we conduct an extensive evaluation in real environments, analyzing the effectiveness of the structure creation mechanism and its robustness under dynamic conditions. Results confirm Brisa as an effcient and robust approach to data dissemination in large dynamic environments.